The Effect of Fire Training Given with Virtual Reality Applications on Individual Awareness - Saklangic, Ugur; Mertoglu, Bülent (Journal of Technical Education and Training, 2023)
The use of virtual reality applications, which entered our lives with the concept of Industry 4.0, in training contributed to increasing the security awareness of individuals and indirectly to developing security culture studies. Obviously, the maximum efficiency that can be obtained in Occupational Health and Safety studies will occur due to behavioural changes in employees. For this reason, it should be ensured that the safety perceptions of the employees are kept at the highest level with appropriate and continuous training. In recent Occupational Health and Safety studies, the importance of developing technology has caused these studies to evolve in a different direction. The study's main purpose in this context is to evaluate whether the fire training given with virtual reality applications contributes to the development of fire safety skills and raising awareness in individuals. This study aims to reveal the teaching of basic fire safety skills to vocational and technical students and academicians at universities, their fire preparedness and their common behaviour in fire situations by using fire extinguishing systems through virtual reality and fire simulation. In the study, 47 questions including one group pre-test post-test, 31 prepared for the scale and 6 interview questions, one of the experimental methods consisting of 10 multiple-choice questions, the scale and face-to-face interviews were conducted. Participants were able to moderately to completely control events in terms of heredity, adaptation/containment, and sensory attachment; In terms of interface quality, it has been determined that they can control events between none and moderate. There is no significant difference between the presence levels and sub-dimensions of the participants in terms of age factor. It can be said that the training with virtual reality is effective in improving the success of the participants in fire training. After the study, it was determined that 38 out of 40 participants increased their success in fire protection subjects. It will be ensured that the fire training given in Turkey will be given more efficiently and effectively by using technological infrastructures. With the feedback received from this study, the existing virtual reality application improvement and virtual reality applications that are planned to be developed will be studied.